Analyzing the Challenges, Options, and Implementation Strategies for Halal Supply Chain Management in Indonesian Cosmetics Sector Companies: A Literature Analysis - Dewie Saktia Ardiantono; Pertiwi; Mushonnifun Faiz Sugihartanto; Berto Mulia Wibawa (UNIVERSITAS NAHDLATUL ULAMA SURABAYA, 2022)
The halal industry's prospects are improving year after year, mirroring the growth of the Muslim population, which is increasing year after year. The halalness of a product is a must for consumers, particularly Muslim consumers. Beginning with food and beverages, fashion, tourism, medicines, cosmetics, media, and so on. The halal cosmetics industry is one of the halal industries that is currently developing. The cosmetics industry is also expanding in Indonesia, and it is now one of the industrial sectors the government focuses on. This is demonstrated by the cosmetic industry being designated as a mainstay sector by the Ministry of Industry of the Republic of Indonesia in the 2015-2035 National Industrial Development Master Plan (RIPN). However, the government's role in developing infrastructure and facilities to implement Halal Supply Chain Management, such as in the cosmetics sector, remains limited. This research aims to identify the barriers to implementing Halal Supply Chain Management in Indonesian cosmetics companies. This study employs a qualitative approach in conjunction with a literature review method. Process, packaging, warehousing, transportation, fundamentals, policy, and technology are all barriers to Halal Supply Chain Management in the Halal Cosmetics sector. While the solution is being developed, warehousing, transportation, fundamentals, and technology are being implemented. Finally, strategy can be found in transportation, fundamentals, and technology.